Determinants of price premium in the Rotterdam groundnut market - Revoredo Giha C.L.; Fletcher S.M. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
The reputation of a firm is based not only on the quality of the goods it offers but also on its reliability as a supplier. The topic is especially important in international trade where one can observe differences in prices of a commodity from different origins, even accounting for the observable characteristics. In this study a model is considered where an importer decides the highest price that he is willing to pay for a commodity from a different origin but with the same characteristics as the one that he is currently importing. If the reliability of both sources is different, one would expert that the less reliable source will receive a lower price. A hedonic price equation using data from a major trader of groundnuts in Rotterdam is estimated. The results indicate that there is a price differential not explained by the product characteristics that favors US groundnuts with respect to Argentine or Chinese groundnuts. The implications of the results are interesting, especially for developing countries trying to capture markets, since part of the price differential is explained by the importer's perception about the supplier reliability. Thus, building a reputation for the product may be a slow process consisting not only of producing the right quality but also of modifying the importer's perception.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)